CONTEMPORARY PROBLEMS OF THE MANAGEMENT OF SOCIAL EXTRA-BUDGETARY FUNDS IN UKRAINE - SEMENOVA, Valentyna; GREMIT, Kateryna (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article studies the problems of managing social non-budgetary funds in Ukraine. The main elements of the system of social extra-budgetary funds in Ukraine are considered, the sources of formation of these funds and the main functions and powers of extra-budgetary funds are studied. It is found that despite the specifics of each type of extra-budgetary funds, their management faces a number of common problems. The main types of problems in the management of extra-budgetary funds are identified: financial, organizational and managerial, demographic, economic and technological. Close interrelationships between different types of problematic aspects are identified, which increase their negative impact. It is determined that in order to overcome the problems of managing social extra-budgetary funds in Ukraine, it is advisable to apply an integrated approach aimed at covering various aspects of the functioning of the social insurance system. The author proposes ways to solve the problems in the main areas, which include, in particular, in the context of financial management: diversification of sources of funding of funds; introduction of a funded pension insurance system; optimization of expenditures of funds; ensuring an increase in the level of efficiency of investment of temporarily free funds. It is determined that important areas for improving the organizational aspects of management are the introduction of modern information technologies; increasing the transparency of funds; improving the risk management system, etc. It is determined that in the context of ensuring effective demographic solutions, it is important to provide incentives for fertility and support for young families; creating conditions for the return of labor migrants. The effectiveness of economic management decisions is related to the fight against the shadow economy and illegal employment; stimulating the development of small and medium-sized businesses; reforming the wage system; optimizing social contribution rates; full digitalization of social fund services; modernization of accounting and reporting systems; and strengthening cybersecurity.